Dispersing agent as well as preparation method and application thereof

By using dispersants of polyphosphate, nitrogen-containing heterocyclic polyester and aromatic amide compounds, the problems of difficulty in dispersing and excessive viscosity of lithium iron phosphate positive electrode slurry are solved, and the internal resistance of the battery is reduced and the circulation performance is improved.

CN119193173APending Publication Date: 2024-12-27SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307990.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems of excessive viscosity and poor coating effect during the dispersion of lithium iron phosphate positive electrode slurry, and the amount of commonly used surfactant is high and is not suitable for high voltage environments, resulting in rapid decline in battery performance.

Method used

By anchoring the surface of lithium iron phosphate, dispersing agents of nitrogen-containing heterocyclic polyester and aromatic group-containing amide compounds, the interface energy is reduced, dispersion is promoted, slurry viscosity is reduced, and uniformity is improved.

Benefits of technology

At an addition amount of less than 0.3%, the slurry viscosity is effectively reduced, the fluidity and dispersion uniformity are improved, the battery circulation performance is improved, and the battery internal resistance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049826630000141
    Figure BDA0005049826630000141
  • Figure BDA0005049826630000151
    Figure BDA0005049826630000151
  • Figure BDA0005049826630000152
    Figure BDA0005049826630000152
Patent Text Reader

Abstract

The invention provides a dispersing agent as well as a preparation method and application thereof. The dispersing agent comprises polyphosphate, nitrogen heterocyclic ring-containing polyester and an aromatic group-containing amide compound. The dispersant is composed of specific compounds, and can effectively reduce the viscosity of the electrode slurry, improve the fluidity and increase the dispersion uniformity of the electrode slurry through a small addition amount, so that the internal resistance of the battery is effectively reduced, and the cycle performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a dispersant and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate plays an important role in power batteries due to its excellent safety performance. The processing method of lithium iron phosphate positive electrode sheets is usually to mix the main material with conductive agents, binders, etc. in a solvent, and make positive electrode slurry by stirring and kneading, and then use extrusion or transfer coating equipment to coat the slurry on carbon-coated aluminum foil, and finally dry and roll the lithium iron phosphate positive electrode sheets.

[0003] For the current dispersion of nano-scale lithium iron phosphate slurry, one solution is to reduce the solid content of the slurry to adapt to the viscosity required for coating, but this solution requires more solvents such as NMP, and takes longer to dry, which greatly increases the cost and reduces the load on the pole piece, which is not conducive to improving the energy density of the battery. The second solution is to add surfactants such as PVP (polyvinyl pyrrolidone) to assist in dispersing the main material, but the amount of surfactants represented by PVP is high, and the unsaturated bonds in the molecular structure are not suitable for the high voltage environment of the positive electrode, which can easily cause side reactions in the pole piece during the cycle, destroy the pole piece structure and cause the battery performance to decline rapidly.

[0004] Therefore, in the process of dispersing lithium iron phosphate positive electrode slurry, there is an urgent need for a suitable dispersant, which can effectively solve the problem of lithium iron phosphate positive electrode slurry dispersion by adding a small amount. Summary of the invention

[0005] The purpose of the present invention is to provide a dispersant and a preparation method and application thereof, and in particular to provide a phosphate dispersant and a preparation method thereof and application thereof in lithium-ion battery homogenization. The dispersant is composed of specific compounds, which can effectively reduce the viscosity of the electrode slurry, improve the fluidity, and increase the dispersion uniformity of the electrode slurry by adding a small amount, thereby effectively reducing the internal resistance of the battery and improving the cycle performance.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a dispersant, which includes polyphosphate, polyester containing nitrogen heterocycles and amide compounds containing aromatic groups.

[0008] The present invention aims at the problems that lithium iron phosphate positive electrode slurry is difficult to disperse, the slurry viscosity is too high at high solid content, and the coating effect is poor. The dispersant provided by the present invention includes a mixture of polyphosphate and nitrogen-containing heterocyclic polyester compounds, wherein the phosphate group in the polyphosphate can anchor the part of the lithium iron phosphate surface that is not completely coated with carbon, the nitrogen-containing heterocyclic can anchor the carbon coating layer, and the polyester as a solvation chain can reduce the interfacial energy, promote dispersion, prevent agglomeration and achieve the effect of stabilizing viscosity; therefore, the polyphosphate and the nitrogen-containing heterocyclic polyester compound can anchor the carbon-coated and non-carbon-coated lithium iron phosphate positive electrode materials, thereby effectively dispersing the lithium iron phosphate positive electrode materials; the amide compound containing an aromatic group is a small molecule compounded in the dispersant, the amide group plays an anchoring role, and the aromatic group has a large steric hindrance, thereby being able to disperse the positive electrode material and reduce the slurry viscosity. Therefore, the dispersant of the present invention can effectively disperse lithium iron phosphate positive electrode slurry, and at an addition amount of less than 0.3%, can effectively reduce the viscosity of the slurry, improve fluidity, and increase the dispersion uniformity of the slurry.

[0009] Preferably, in the dispersant, the content of polyphosphate ester is 30-50wt%, for example, 30wt%, 35wt%, 40wt% or 50wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] Preferably, in the dispersant, the content of the nitrogen-containing heterocyclic polyester is 20-40 wt%, for example, 20 wt%, 30 wt% or 40 wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] Preferably, in the dispersant, the content of the aromatic amide compound is 10-30wt%, for example, 10wt%, 20wt%, 25wt% or 30wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] Preferably, the polyphosphate comprises polyethylene glycol phosphate.

[0013] Preferably, the nitrogen-containing heterocyclic polyester includes any one of polyethylene glycol pyrrolidone carboxylate, polyethylene glycol pyrrolidone carboxylate, or polyethylene glycol pyridinic acid ester, or a combination of at least two thereof.

[0014] Preferably, the aromatic group-containing amide compound includes any one of N-phenylacetamide, p-benzamide, p-terephthalamide, or phenylacrylamide, or a combination of at least two thereof.

[0015] Preferably, the raw materials for preparing the dispersant include organic matter and phosphorus-containing compounds, and the organic matter includes N-heterocyclic acids, alcohol polymers and aromatic amide compounds.

[0016] Preferably, the mass ratio of the N-heterocyclic acid, the alcohol polymer and the aromatic amide compound is 1:(2-5):(0.4-0.8), for example, it can be 1:2:0.4, 1:3:0.6, 1:4:0.8, 1:5:0.5 or 1:5:0.8, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] The mass ratio of the N-heterocyclic acid, alcohol polymer and aromatic amide compound of the present invention will affect the content of polyphosphate, nitrogen-containing heterocyclic polyester and aromatic amide small molecules in the dispersant, thereby affecting the dispersing effect of the dispersant. If the alcohol polymer is too little, the dispersant lacks solvation chains and the viscosity stabilization effect is poor; if the alcohol polymer is too much, the anchoring group is lacking and the dispersion effect is poor; if the content of aromatic amide small molecules is too little, the viscosity reduction effect is not obvious; if the content of aromatic amide compounds is too much, the internal resistance of the battery cell is affected.

[0018] Preferably, the mass ratio of the N-heterocyclic acid to the phosphorus-containing compound is 1:(0.1-0.3), for example, 1:0.1, 1:0.2 or 1:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] The mass ratio of the N-heterocyclic acid to the phosphorus-containing compound of the present invention affects the content of the nitrogen-heterocyclic polyester and polyphosphate. Preferably, the mass ratio of the N-heterocyclic acid to the phosphorus-containing compound is within a specific range.

[0020] Preferably, the N-heterocyclic acid includes any one of pyrrolidonecarboxylic acid, pyrrolecarboxylic acid or picolinic acid, or a combination of at least two thereof.

[0021] Preferably, the aromatic amide compound includes any one of N-phenylacetamide, p-benzamide, terephthalamide or phenylacrylamide, or a combination of at least two thereof.

[0022] Preferably, the alcohol polymer includes any one of polyethylene glycol, polypropylene glycol or polyglycerol, or a combination of at least two of them.

[0023] Preferably, the phosphorus-containing compound comprises phosphorus pentoxide.

[0024] Preferably, the raw materials for preparing the dispersant also include a catalyst and an initiator.

[0025] Preferably, the catalyst comprises p-toluenesulfonic acid.

[0026] Preferably, the initiator comprises azobisisobutyronitrile and / or azobisisoheptanenitrile.

[0027] In a second aspect, the present invention provides a method for preparing the dispersant as described in the first aspect, the preparation method comprising the following steps:

[0028] (1) mixing and reacting an alcohol polymer, a solvent and a phosphorus-containing compound to obtain a reaction liquid;

[0029] (2) A second mixing of the N-heterocyclic acid, the aromatic amide compound, the initiator and the reaction liquid of step (1) is performed to obtain the dispersant.

[0030] The present invention firstly blends an alcohol polymer, a phosphorus-containing compound and an NMP solvent to obtain a polyphosphate compound, and then performs a second mixing of the reaction solution with an acid containing an N-heterocyclic ring, an aromatic amide compound and an initiator, so that the acid containing the N-heterocyclic ring and part of the alcohol polymer undergo a dehydration condensation reaction to obtain a nitrogen-containing heterocyclic polyester compound; meanwhile, the preparation method of the present invention is environmentally friendly, does not need to control the environmental humidity, and can greatly reduce the production cost.

[0031] In the preparation method of the present invention, the preparation is carried out according to the formula amount in the preparation raw materials.

[0032] Preferably, a catalyst is also added during the first mixing in step (1).

[0033] Preferably, the catalyst comprises p-toluenesulfonic acid.

[0034] Preferably, the reaction temperature in step (1) is 130-170°C, for example, 130°C, 140°C, 150°C, 160°C or 170°C, and the reaction time is 1-2h, for example, 1h, 1.5h or 2h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, in step (2), the temperature of the second mixing is 60-90°C, for example, 60°C, 70°C, 80°C or 90°C, and the time is 2-4h, for example, 2h, 3h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, a solvent is also added during the second mixing in step (2).

[0037] Preferably, the solvent comprises N-methylpyrrolidone.

[0038] Preferably, the initiator in step (2) comprises azobisisobutyronitrile and / or azobisisoheptanenitrile.

[0039] Preferably, the second mixing in step (2) comprises adding an N-heterocyclic acid, an aromatic amide compound and a solvent to the reaction liquid in step (1), stirring at 60-90° C., then adding an initiator and stirring at a low speed for 2-4 hours, cooling and filtering to obtain the dispersant.

[0040] In a third aspect, the present invention provides a positive electrode slurry, which includes a lithium iron phosphate positive electrode material and the dispersant as described in the first aspect.

[0041] Preferably, the content of the dispersant is less than 0.3wt% of the non-solvent component in the positive electrode slurry, for example, it can be 0.3wt%, 0.2wt%, 0.1wt% or 0.05wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.1-0.2wt%.

[0042] The content of the dispersant in the positive electrode slurry of the present invention only needs to be added to 0.3wt% to effectively play a dispersing role. If the content of the dispersant is added too much, since the dispersant includes non-conductive components and the material is relatively brittle, excessive addition will affect the internal resistance and DCR of the battery. At the same time, at the end of the cycle, the interface of the positive electrode plate will be poor and easy to fall off, thereby affecting the number of cycles.

[0043] Preferably, the positive electrode slurry comprises LFP, a conductive agent, a binder and a dispersant in a mass ratio of (95-97):(1-2):(2-3):(0.1-0.2), for example, it can be 95.5:1.5:2.9:0.1, 96.8:1:2:0.2 or 95.9:2:2:0.1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In a fourth aspect, the present invention provides a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a current collector and a positive electrode active layer on at least one side surface of the current collector, wherein the positive electrode active layer is obtained from the positive electrode slurry as described in the third aspect.

[0045] Preferably, the battery also includes a negative electrode plate, which includes artificial graphite, SP, CMC and SBR in the ratio of (94-96):(0.8-2.0):(1.0-1.8):(1.0-2.5), for example, it can be 94:2.0:1.8:2.2, 95:1.5:1.5:2 or 96:0.8:1.7:1.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention can anchor not only the lithium iron phosphate positive electrode material that is not carbon-coated, but also the carbon-coated lithium iron phosphate positive electrode material through polyphosphate ester, nitrogen-containing heterocyclic polyester and aromatic group-containing polyamide compound, improve steric hindrance, thereby effectively exerting the dispersion effect, and can effectively reduce the viscosity of the slurry, improve the fluidity, increase the dispersion uniformity of the slurry at an addition amount of less than 0.3%, solve the problems of difficulty in dispersing lithium iron phosphate positive electrode slurry, too high slurry viscosity at high solid content, and poor coating effect. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] Example 1

[0050] This embodiment provides a dispersant, which includes 50 wt % of polyethylene glycol phosphate, 30 wt % of polyethylene glycol pyrrolidone carboxylate and 20 wt % of N-phenylacetamide;

[0051] The raw materials for preparing the dispersant include pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide in a mass ratio of 1:3:0.6, and also include phosphorus pentoxide, p-toluenesulfonic acid and azobisisobutyronitrile, and the mass ratio of the pyrrolidone carboxylic acid to phosphorus pentoxide is 1:0.2;

[0052] The preparation method of the dispersant comprises the following steps:

[0053] (1) First, 150 g of polyethylene glycol and 100 g of NMP were added to a mixed monomer kettle, stirred at room temperature for 30 minutes, and then 10 g of phosphorus pentoxide and 15 g of p-toluenesulfonic acid were added, and the mixture was reacted at 150° C. for 1 hour for dehydration condensation to generate a polyphosphate mixture, thereby obtaining a reaction liquid;

[0054] (2) Then, 50 g of pyrrolidone carboxylic acid, 30 g of N-phenylacetamide and 130 g of NMP were added to the reaction solution in step (1), and the mixture was stirred at 60° C. for 1 hour. Then, 10 g of azobisisobutyronitrile was added as an initiator, and the mixture was stirred at a low speed for 4 hours. The mixture was cooled and filtered to obtain the dispersant.

[0055] Example 2

[0056] This embodiment provides a dispersant, which includes 40 wt % of polyethylene glycol phosphate, 40 wt % of polyethylene glycol pyrrolidone carboxylate and 20 wt % of N-phenylacetamide;

[0057] The raw materials for preparing the dispersant include pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide in a mass ratio of 1:3:0.6, and also include phosphorus pentoxide, p-toluenesulfonic acid and azobisisobutyronitrile, and the mass ratio of the pyrrolidone carboxylic acid to phosphorus pentoxide is 1:0.15;

[0058] The preparation method of the dispersant comprises the following steps:

[0059] (1) First, 150 g of polyethylene glycol and 100 g of NMP were added to a mixed monomer kettle, stirred at room temperature for 30 minutes, and then 7.5 g of phosphorus pentoxide and 15 g of p-toluenesulfonic acid were added, and the mixture was reacted at 150° C. for 1 hour for dehydration condensation to generate a polyphosphate mixture, thereby obtaining a reaction liquid;

[0060] (2) Then, 50 g of pyrrolidone carboxylic acid, 30 g of N-phenylacetamide and 130 g of NMP were added to the reaction solution in step (1), and the mixture was stirred at 60° C. for 1 hour. Then, 10 g of azobisisobutyronitrile was added as an initiator, and the mixture was stirred at a low speed for 4 hours. The mixture was cooled and filtered to obtain the dispersant.

[0061] Example 3

[0062] This embodiment provides a dispersant, which includes 30 wt % of polyethylene glycol phosphate, 40 wt % of polyethylene glycol pyrrolidone carboxylate and 30 wt % of N-phenylacetamide;

[0063] The raw materials for preparing the dispersant include pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide in a mass ratio of 1:3:0.8, and also include phosphorus pentoxide, p-toluenesulfonic acid and azobisisobutyronitrile, and the mass ratio of the pyrrolidone carboxylic acid to phosphorus pentoxide is 1:0.12;

[0064] The preparation method of the dispersant comprises the following steps:

[0065] (1) First, 150 g of polyethylene glycol and 100 g of NMP were added to a mixed monomer kettle, stirred at room temperature for 30 minutes, and then 6 g of phosphorus pentoxide and 15 g of p-toluenesulfonic acid were added, and the mixture was stirred at 150° C. for 1 hour to cause dehydration condensation to generate a polyphosphate mixture, thereby obtaining a reaction liquid;

[0066] (2) Then, 50 g of pyrrolidone carboxylic acid, 40 g of N-phenylacetamide and 130 g of NMP were added to the reaction solution in step (1), and the mixture was stirred at 60° C. for 1 hour. Then, 10 g of azobisisobutyronitrile was added as an initiator, and the mixture was stirred at a low speed for 4 hours. The mixture was cooled and filtered to obtain the dispersant.

[0067] Example 4

[0068] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:2:0.4 to adapt the dispersant.

[0069] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0070] Example 5

[0071] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:5:0.4 to adapt the dispersant.

[0072] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0073] Example 6

[0074] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:2:0.8 to make the dispersant adaptable;

[0075] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0076] Example 7

[0077] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:5:0.8 to adapt the dispersant.

[0078] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0079] Example 8

[0080] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:3:0.2 to adapt the dispersant.

[0081] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0082] Example 9

[0083] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid, polyethylene glycol and N-phenylacetamide is 1:3:1 to adapt the dispersant;

[0084] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0085] Example 10

[0086] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid to phosphorus pentoxide is 1:0.05 to adapt the dispersant.

[0087] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0088] Embodiment 11

[0089] This embodiment provides a dispersant, which is the same as that of Embodiment 1 except that the mass ratio of pyrrolidone carboxylic acid to phosphorus pentoxide is 1:0.5 to adapt the dispersant.

[0090] The preparation method of the dispersant is the same as that of Example 1 except that the formula amount of the preparation raw materials is adaptively changed.

[0091] Comparative Example 1

[0092] This comparative example provides a dispersant, which is the same as Example 1 except that the preparation raw material does not contain phosphorus pentoxide, so that the dispersant does not contain polyphosphate;

[0093] The preparation method of the dispersant is the same as that of Example 1 except that phosphorus pentoxide is not added in step (1).

[0094] Comparative Example 2

[0095] This comparative example provides a dispersant, which is the same as Example 1 except that the dispersant does not contain an N-phenylacetamide compound;

[0096] The preparation method of the dispersant is the same as that of Example 1 except that N-phenylacetamide is not added in step (2).

[0097] Comparative Example 3

[0098] This comparative example provides a dispersant, which is the same as Example 1 except that the dispersant does not contain polyethylene glycol pyrrolidone carboxylate;

[0099] The preparation method of the dispersant is the same as that of Example 1 except that pyrrolidone carboxylic acid is not added in step (2).

[0100] Application Example 1

[0101] This application example provides a positive electrode sheet, and the preparation method of the positive electrode sheet includes the following steps:

[0102] LFP, SP, PVDF and the dispersant described in Example 1 were added to a double planetary agitator in a mass ratio of 96.8:1:2:0.2, and a certain amount of NMP solvent was added and dispersed at room temperature to obtain a positive electrode slurry. The prepared positive electrode slurry was coated on both sides of the aluminum foil by transfer coating, and baked in an oven at a temperature of 120°C for 3 minutes to obtain the positive electrode sheet.

[0103] Application Example 2-11

[0104] Application Example 2-11 provides a positive electrode plate. The preparation method of the positive electrode plate is the same as that of Application Example 1, except that the dispersant of Example 2-11 is used.

[0105] Application Example 12

[0106] This application example provides a positive electrode sheet. The preparation method of the positive electrode sheet is the same as that of Application Example 1, except that the mass ratio of LFP, SP, PVDF and the dispersant described in Example 1 is 96.95:1:2:0.05.

[0107] Application Example 13

[0108] This application example provides a positive electrode sheet. The preparation method of the positive electrode sheet is the same as that of Application Example 1, except that the mass ratio of LFP, SP, PVDF and the dispersant described in Example 1 is 96.7:1:2:0.3.

[0109] Comparative application example 1

[0110] This comparative application example provides a positive electrode plate. The preparation method of the positive electrode plate is the same as that of Application Example 1 except that the dispersant of Comparative Example 1 is used.

[0111] Comparative Application Example 2

[0112] This comparative application example provides a positive electrode plate. The preparation method of the positive electrode plate is the same as that of Application Example 1 except that the dispersant of Comparative Example 2 is used.

[0113] Comparative Application Example 3

[0114] This comparative application example provides a positive electrode plate. The preparation method of the positive electrode plate is the same as that of Application Example 1 except that the dispersant of Comparative Example 3 is used.

[0115] Comparative Application Example 4

[0116] This comparative application example provides a positive electrode sheet. The preparation method of the positive electrode sheet is the same as that of Application Example 1, except that no dispersant is added and the mass ratio of LFP, SP and PVDF is 97:1:2.

[0117] The positive electrode sheets, separators and negative electrode sheets of the above application examples and comparative application examples are stacked in order, so that the separator is placed between the positive electrode sheets and the negative electrode sheets to play an isolating role, and the stacked sheets are wound to obtain a bare cell; the bare cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, forming, shaping and other processes; wherein the negative electrode sheet adopts an artificial graphite formula, and the negative electrode slurry includes: artificial graphite, SP, CMC and SBR in a weight ratio of 95:1.5:1.5:2, and the electrolyte is a lithium-ion battery containing LiPF 6 The isolation membrane is a polyethylene film.

[0118] Lithium-ion battery testing:

[0119] Basic electrical performance test: At 25°C, the lithium-ion battery is first pre-charged with a small current for 180 minutes, fully charged to 3.65V at 0.33C constant current, and constant voltage to 0.05C, and then fully discharged to 2.5V at 0.33C. The ratio of discharge capacity to charge capacity is calculated to obtain the initial efficiency.

[0120] Dynamic performance test: The lithium-ion battery is tested at 25°C and -20°C using the standard HPPC test method to measure the charge and discharge DCR at different SOCs, mainly evaluating the charge and discharge DCR at 50%.

[0121] Cycle performance test: At 25°C, the lithium-ion battery is charged at a rate of 3C and discharged at a rate of 1C, and a full charge and discharge cycle test is performed until the capacity of the lithium-ion battery decays to 80% of the initial capacity, and the number of cycles is recorded.

[0122] Cathode slurry test:

[0123] Solid content: Dry in an oven, weigh 2g±0.5g of the sample with an electronic scale accurate to 0.1mg, record the mass as m2, put it in a weighing flat-bottomed dish with a mass of m1, spread it as flat as possible, and then bake it in a constant temperature oven at 120±2℃ for 2h, then cool it in a dryer for 30min and weigh its mass as m3. The calculated solid content is (m3-m1) / m2*100%.

[0124] Viscosity test: Use a Brookfield viscometer to test the viscosity of the sample by combining different rotors and speeds.

[0125] Positive electrode test:

[0126] Peel strength: Refer to GB / T 2792-2014 standard.

[0127] Electrode resistivity: Two-probe method, place the terminals at both ends of the sample, input AC voltage signal, collect the current at both ends of the sample, thereby obtaining the sample resistance, and the sample resistivity is obtained through conversion relationship.

[0128] The test results are shown in Table 1 and Table 2:

[0129] Table 1

[0130]

[0131]

[0132] Table 2

[0133]

[0134]

[0135] From the above table we can see that:

[0136] (1) It can be seen from Application Example 1 and Comparative Application Example 1 that the dispersant of the present invention contains polyphosphate, which can anchor lithium iron phosphate positive electrode materials, thereby further improving the dispersibility of lithium iron phosphate positive electrode materials and the stability of slurry viscosity, thereby improving the electrochemical performance of the battery; It can be seen from Application Example 1 and Comparative Application Example 2 that the dispersant of the present invention also contains aromatic amide compounds, which can further enhance the steric hindrance of the dispersant, have a significant viscosity reduction and solidification effect on lithium iron phosphate positive electrode slurry, and can improve the electrochemical performance of the battery cell to a certain extent; It can be seen from Application Example 1 and Comparative Application Example 3 that nitrogen-containing heterocyclic polyester can anchor the carbon coating layer, and polyester as a solvation chain can reduce the interfacial energy, promote slurry dispersion and improve stability, thereby reducing slurry viscosity rebound.

[0137] (2) It can be seen from Application Example 1 and Comparative Application Example 4 that no dispersant is added to the positive electrode slurry in Comparative Application Example 4, and the discharge viscosity of the positive electrode slurry is much higher than that in Application Example 1, while the discharge viscosity of the application examples of the present invention is relatively stable, between 5500-6500 cP, which is nearly 70-90% higher than some application examples, proving that the dispersant of the present invention has a good effect of improving solidification and reducing viscosity, and the 24h viscosity rebound data of Comparative Application Example 4 is nearly 300-400% higher than some application examples, which also confirms that the dispersant of the present invention has an outstanding viscosity stabilizing effect; and the battery internal resistance of Comparative Application Example 4 is reduced by about 10%, the DCR at room temperature and low temperature is also reduced, and the 3C / 1C room temperature cycle number is increased by about 8%. Therefore, the addition of the dispersant of the present invention makes the positive electrode slurry more evenly dispersed and reduces the agglomeration of substances such as carbon black, thereby improving the battery internal resistance, DCR and cycle.

[0138] (3) It can be seen from Application Examples 1 and 8-9 that the amount of aromatic amide compounds added to the raw materials prepared by the present invention will affect the effect of the dispersant. A smaller amount will affect the solidification and viscosity reduction results, while a larger amount will affect the electrode resistivity and battery cell cycle. It can be seen from Application Examples 1 and 10-11 that the amount of phosphorus-containing compounds added to the raw materials prepared by the present invention will affect the content of polyphosphate in the dispersant, thereby affecting the effect of the dispersant. A smaller amount will affect the dispersant viscosity stabilization results, while a larger amount will affect the electrode resistivity and battery cell cycle. Cycle; It can be seen from Application Examples 1 and 12-13 that the dispersant of the present invention can be added in a relatively small amount to play an effective role. If the proportion of the dispersant in the positive electrode slurry is increased, although it has little effect on the viscosity rebound of the slurry, since the dispersant is a non-conductive component, excessive addition significantly increases its electrode resistivity, which is increased by about 20-30%, and excessive addition will affect the battery internal resistance and DCR. At the same time, at the end of the cycle, the interface of the positive electrode sheet will be poor and easy to fall off, thereby affecting the number of cycles, and too little addition of the dispersant will reduce the dispersion effect.

[0139] In summary, the present invention provides a dispersant and a preparation method and application thereof. The dispersant is composed of specific compounds, which can effectively reduce the viscosity of the electrode slurry, improve the fluidity, and increase the dispersion uniformity of the electrode slurry by adding a small amount, thereby effectively reducing the internal resistance of the battery and improving the cycle performance.

[0140] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A dispersant, characterized in that: The dispersant includes polyphosphate, polyester containing nitrogen heterocycle and amide compound containing aromatic group.

2. The dispersant according to claim 1, characterized in that In the dispersant, the content of polyphosphate is 30-50wt%; Preferably, in the dispersant, the content of the nitrogen-containing heterocyclic polyester is 20-40 wt %; Preferably, the content of the aromatic amide compound in the dispersant is 10-30wt%; Preferably, the polyphosphate comprises polyethylene glycol phosphate; Preferably, the nitrogen-containing heterocyclic polyester comprises any one or a combination of at least two of polyethylene glycol pyrrolidone carboxylate, polyethylene glycol pyrrolidone carboxylate or polyethylene glycol pyridinate; Preferably, the aromatic group-containing amide compound includes any one of N-phenylacetamide, p-benzamide, terephthalamide or phenylacrylamide, or a combination of at least two thereof.

3. The dispersant according to claim 1 or 2, characterized in that The raw materials for preparing the dispersant include organic matter and phosphorus-containing compounds, and the organic matter includes N-heterocyclic acids, alcohol polymers and aromatic amide compounds; Preferably, the mass ratio of the N-heterocyclic acid, the alcohol polymer and the aromatic amide compound is 1:(2-5):(0.4-0.8); Preferably, the mass ratio of the N-heterocyclic acid to the phosphorus-containing compound is 1:(0.1-0.3).

4. The dispersant according to claim 3, characterized in that The N-heterocyclic acid includes any one of pyrrolidonecarboxylic acid, pyrrolecarboxylic acid or picolinic acid, or a combination of at least two thereof; Preferably, the aromatic amide compound includes any one or a combination of at least two of N-phenylacetamide, p-benzamide, terephthalamide or phenylacrylamide; Preferably, the alcohol polymer includes any one of polyethylene glycol, polypropylene glycol or polyglycerol, or a combination of at least two thereof; Preferably, the phosphorus-containing compound comprises phosphorus pentoxide.

5. A method for preparing a dispersant according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing and reacting an alcohol polymer, a solvent and a phosphorus-containing compound to obtain a reaction liquid; (2) A second mixing of the N-heterocyclic acid, the aromatic amide compound, the initiator and the reaction liquid of step (1) is performed to obtain the dispersant.

6. The preparation method according to claim 5, characterized in that: Step (1) A catalyst is also added during the first mixing; Preferably, the catalyst comprises p-toluenesulfonic acid; Preferably, the reaction temperature in step (1) is 130-170° C. and the reaction time is 1-2 h.

7. The preparation method according to claim 5 or 6, characterized in that: Step (2) the second mixing temperature is 60-90°C and the time is 2-4h; Preferably, in step (2), a solvent is also added during the second mixing; Preferably, the initiator in step (2) comprises azobisisobutyronitrile and / or azobisisoheptanenitrile.

8. A positive electrode slurry, characterized in that: The positive electrode slurry comprises a lithium iron phosphate positive electrode material and a dispersant as claimed in any one of claims 1 to 4.

9. The positive electrode slurry according to claim 8, characterized in that: The content of the dispersant accounts for less than 0.3 wt % of the non-solvent components in the positive electrode slurry, preferably 0.1-0.2 wt %.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active layer on at least one side surface of the current collector, and the positive electrode active layer is obtained from the positive electrode slurry as claimed in claim 8 or 9.